Managing productivity in Universiti Malaysia Pahang: Rethinking the whom, which, what, and whose of productivity - Nor Alisa, Mohd Damanhuri; Mohd Rusllim, Mohamed; Siti Zanariah, Satari; N., Masngut; Roslinazairimah, Zakaria; Rozieana, Khairuddin (Universiti Malaysia Pahang, 2019)
Drawing on reviews of scholarly literature, this study suggests rethinking productivity in Universiti Malaysis Pahang (UMP) along four dimensions: the productivity of whom, productivity for which unit of analysis, productivity according to what functions, and productivity in whose interests. It offers principles for promoting enlightened discussion and pursuit of productivity of academic staff at UMP. In contrast to the dominant discussion, which emphasises focus, centralised standard measures, and accountability, the bias unfairness in this study is toward balance, decentralised diversity, and recalibration. Academic Differentiated Career Pathways (ADCAP) suggest the ideal is not for academic staff and faculties to produce to centrally managed objectives but for all individuals and units faculties to manage individually and collectively to design their work to improve their productivity along multiple dimensions.